Pengenalan STEMM Untuk Siswa MAN 1 Kota Bengkulu dan Posisi Ilmu Kimia di Masa Kini dan Masa Depan - Asdim, Asdim; Gustian, Irfan; Taruna Asral, Suci Sukma; Mawakhid, Oki Rokhim; Nendo, Felicia Febyola; Wibowo, Yudhistira Panca (Jurnal Pengabdian Masyarakat Pinang Masak, 2026)
This Community Service (PPM) activity aims to increase the understanding and interest of 12th grade students of MAN 1 Kota Bengkulu in the concept of STEMM (Science, Technology, Engineering, Mathematics, and Medicine) and introduce the strategic role of chemistry in the development of current and future technology. The activity was carried out through the delivery of interactive materials, discussions, and the implementation of the "Magic Paper" mini experiment as a simple demonstration based on the concept of natural indicators. The results of the implementation showed that students gave a very positive response, marked by high enthusiasm in the question and answer session, discussions, and active involvement in the experiment. The mini experiment was proven to help strengthen students' understanding of the application of chemistry in everyday life and its relevance within the STEMM framework. Overall, this activity succeeded in increasing scientific literacy, fostering curiosity, and broadening students' insights regarding STEMM and the position of chemistry in the advancement of science and technology.